HDAC Inhibitor Titration of Transcription and Axolotl Tail Regeneration - Voss, S. Randal; Smith, Jeramiah J.; Cecil, Raissa F.; Kabangu, Mirindi; Duerr, Timothy J.; Monaghan, James R.; Timoshevskaya, Nataliya; Ponomareva, Larissa V.; Thorson, Jon S.; Veliz-Cuba, Alan; Murrugarra, David (Frontiers in Cell and Developmental Biology, 2021)
New patterns of gene expression are enacted and regulated during tissue regeneration. Histone deacetylases (HDACs) regulate gene expression by removing acetylated lysine residues from histones and proteins that function directly or indirectly in transcriptional regulation. Previously we showed that romidepsin, an FDA-approved HDAC inhibitor, potently blocks axolotl embryo tail regeneration by altering initial transcriptional responses to injury. Here, we report on the concentration-dependent effect of romidepsin on transcription and regeneration outcome, introducing an experimental and conceptual framework for investigating small molecule mechanisms of action. A range of romidepsin concentrations (0 – 10 M) were administered from 0 – 6 or 0 – 12 hours post amputation (HPA) and distal tail tip tissue was collected for gene expression analysis. Above a threshold concentration, romidepsin potently inhibited regeneration. Sigmoidal and biphasic transcription response curve modeling identified genes with inflection points aligning to the threshold concentration defining regenerative failure verses success. Regeneration inhibitory concentrations of romidepsin increased and decreased the expression of key genes. Genes that associate with oxidative stress, negative regulation of cell signaling, negative regulation of cell cycle progression, and cellular differentiation were increased, while genes that are typically up-regulated during appendage regeneration were decreased, including genes expressed by fibroblast-like progenitor cells. Using single-nuclei RNA-Seq at 6 HPA, we found that key genes were altered by romidepin in the same direction across multiple cell types. Our results implicate HDAC activity as a transcriptional mechanism that operates across cell types to regulate the alternative expression of genes that associate with regenerative success versus failure outcomes.